Strategi Mitigasi Kerentanan Kesehatan Mental Siswa di MTs Muhammadiyah 02 Purbalingga - Setiadi, Yanuar Abdillah; Hanif, Muh (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
This study aims to understand the mitigation strategies in addressing students' mental health vulnerability at MTs Muhammadiyah 02 Purbalingga. Using a qualitative approach and field research method, data was collected through in-depth interviews, direct observation, and school policy documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The focus of the research included factors such as excessive use of social media, age gap between teachers and students, and less adaptive communication patterns. The results showed that on average students spend more than six hours a day accessing social media and online games, which has an impact on declining learning focus, mental resilience and academic motivation. The age gap between teachers and students widens the differences in perspectives and ways of communicating, thus worsening relationships in the classroom. In addition, rigid teacher communication patterns are unable to meet the emotional needs of digital generation students. The strategies applied by schools include the integration of Islamic values in learning, strengthening character education, limiting the use of gadgets during school hours, and providing counseling services. This study recommends innovation in Islamic education management to be more adaptive to technological developments and social dynamics. Schools need to design strategies that integrate Islamic values with a healthy digital-based learning approach. Character strengthening and digital literacy should be an important part of the Islamic education curriculum. In addition, communication patterns between teachers and students need to be adjusted to the emotional needs of the current generation to be more dialogic and empathetic.